ЕUROPEAN SOCIETY IN THE POETRY BY V.F. KHODASEVICH IN THE 1920s AND 1930s (Philological Studies, 2021)
The paper considers the image of “the man of the masses” in emigration poems by V.F. Khodasevich. In his latest book of poetry “European Night” and other emigration poems several portraits of people of the masses can be discovered: men, women, single people, married couples, old people, children as well as collective images. Thereby in “German” and “French” poetry Khodasevich creates a model of European society in the period between two world wars. Moreover, in works written in Germany and France the poet addresses the conflict between the main character (the poet) and the man of the masses. This conflict is based on the impossibility of the latter to understand art. The author of the paper concludes that in Khodasevich’s emigration poems European society has no future.
Keywords: V.F. Khodasevich, European city, European society, “man of the masses”, emigration